Injury prevention exercise programs for professional soccer: Understanding the perceptions of the end-users - O'Brien, J.; Finch, C. F. (Clinical Journal of Sport Medicine, 2017)
Objective: To evaluate the perceptions of professional soccer players and staff members toward injury prevention exercise programs (IPEPs). Design: Self-report survey. Setting: Four professional soccer teams in 4 different countries. Participants: 126 players, coaches, physiotherapists, and fitness coaches were invited to participate, with 72 respondents. Main Outcome Measures: Web-based survey detailing perceptions of lower limb (LL) injury susceptibility and seriousness, the value of IPEPs in general, and more specifically the International Federation of Association Football (FIFA) 11+. Results: The vast majority of the respondents believed that professional soccer players are at high risk of LL injuries (93%) and that players should perform evidence-based injury prevention exercises (98%). They also agreed that LL injuries can shorten a player's career (85%), cause physical problems later in life (82%), and negatively impact on team performance (77%). However, perceptions varied across teams regarding which types of injury prevention exercises are effective, who holds responsibility for injury prevention, and when IPEPs should be performed. Specific knowledge of the FIFA 11+ was very low and 47% of respondents believed the program would need modification for use in their team. Conclusions: Players and staff members in professional soccer teams strongly support the use of evidence-based IPEPs. However, perceptions vary considerably between teams regarding which exercises can prevent injuries, who holds the responsibility for injury prevention, and when preventive exercises should be performed. Enhancing the ultimate impact of IPEPs in professional soccer requires a detailed understanding of each team's specific implementation context. ABSTRACT FROM AUTHOR